2019
DOI: 10.1177/2058739219861570
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ajwa dates in ameliorating diclofenac sodium-induced nephrotoxicity and cardiovascular risk factors in mice

Abstract: The study aims at evaluating the protective effects of Ajwa dates extract against diclofenac sodium (DFS)-induced nephrotoxicity. A total of 30 male albino mice were divided into three groups. Group 1 received water per oral gavage for 14 days and saline per intra-peritoneal (IP) dose for the days 12–14. Group 2 received water like Group 1 and a daily IP dose of DFS for the days 12–14. Group 3 received 1 gm/kg Ajwa extract in water for 14 days and a daily IP dose for the days 12–14. Biochemical investigation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Glomerular lesions, congestion of renal vessels in the cortex, and signs of inflammation were also present. These findings are in agreement with previous publications which have also documented similar observations of kidney injury induced by diclofenac [9,19,[47][48][49]. The study by Yasmeen et al reported proximal tubule dilatation, degenerative changes in the lining epithelial cells of these tubules, where the nuclei of some cells appeared condensed, and congestion of blood vessels in the cortical area with few inflammatory foci [50].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Glomerular lesions, congestion of renal vessels in the cortex, and signs of inflammation were also present. These findings are in agreement with previous publications which have also documented similar observations of kidney injury induced by diclofenac [9,19,[47][48][49]. The study by Yasmeen et al reported proximal tubule dilatation, degenerative changes in the lining epithelial cells of these tubules, where the nuclei of some cells appeared condensed, and congestion of blood vessels in the cortical area with few inflammatory foci [50].…”
Section: Discussionsupporting
confidence: 92%
“…This simple protocol has been implemented by earlier published studies [9,34]. Animals in the Dic groups were injected with 50 mg/kg of Diclofenac Sodium I.M.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations